1997
DOI: 10.1086/304078
|View full text |Cite
|
Sign up to set email alerts
|

High‐Velocity Rain: The Terminal Velocity Model of Galactic Infall

Abstract: A model is proposed for determining the distances to falling interstellar clouds in the galactic halo by measuring the cloud velocity and column density and assuming a model for the vertical density distribution of the Galactic interstellar medium. It is shown that falling clouds with N (H I) < ∼ 10 19 cm −2 may be decelerated to a terminal velocity which increases with increasing height above the Galactic plane. This terminal velocity model correctly predicts the distance to high velocity cloud Complex M and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 51 publications
6
77
1
Order By: Relevance
“…He found that if the cold clouds fall ballistically, their vertical highest velocities could reach -80 km s −1 and up to -150 km s −1 . Similar results are found if we use the terminal velocity equation from Benjamin & Danly (1997) to calculate the terminal velocities of free-falling clouds at the diskhalo interface. This is consistent with the high velocity v acc = 110 km s −1 found in our Accreting Layer model.…”
Section: The Origin Of the Ionized Gas Inflowsupporting
confidence: 81%
“…He found that if the cold clouds fall ballistically, their vertical highest velocities could reach -80 km s −1 and up to -150 km s −1 . Similar results are found if we use the terminal velocity equation from Benjamin & Danly (1997) to calculate the terminal velocities of free-falling clouds at the diskhalo interface. This is consistent with the high velocity v acc = 110 km s −1 found in our Accreting Layer model.…”
Section: The Origin Of the Ionized Gas Inflowsupporting
confidence: 81%
“…The WHIM was formed by shock heating in the early stages of cosmological structure formation and should pervade the connected large-scale structure predicted to form (Melott et al 1983) in the cold dark matter scenario. Our Galaxy moves at the speed of $150-200 km s À1 toward the Virgo Cluster ( Williams et al 2006b;Benjamin & Danly 1997), which is close to the Galactic north pole.…”
Section: Galactic Shock Modelmentioning
confidence: 97%
“…These short lifetimes are a problem unless the clouds are continually regenerated on short timescales. In addition, some HVCs that are not clearly linked to satellite accretion have velocities that cannot be reached through gravitational acceleration within several hundred Myr (Benjamin & Danly, 1997;Peek et al, 2007). The exact lifetime of a cloud depends on several factors such as cloud density, halo density, and velocity, but the total mass of the cloud seems to be one of the largest factors increasing their lifetimes (Heitsch & Putman, 2009;Kwak et al, 2011).…”
Section: Halo Cloud Survivalmentioning
confidence: 99%